1987
DOI: 10.1182/blood.v69.5.1381.1381
|View full text |Cite
|
Sign up to set email alerts
|

Purging leukemic cells from simulated human remission marrow with alkyl- lysophospholipid

Abstract: Alkyl-lysophospholipids (ALP) are analogues of 2- lysophosphatidylcholine that have been reported to have selective antitumor activity. These compounds could potentially be useful in purging bone marrow of leukemic cells in autologous marrow transplantation in acute leukemia. To determine the efficacy of pharmacological purging by ALP, we have designed a human assay system to mimic the conditions expected in the clinical setting of autotransplantation using remission marrow. A simulated remission marrow (SRM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Synthetic ether phospholipids seem to constitute a novel class of anti-tumour agents [1]. The ether lipid 1-octadecyl-2-methyl-racglycero-3-phosphocholine (ET-1 8-OCH3) is a synthetic analogue of 2-lysophosphatidylcholine and acts as an strong anti-tumour agent [2][3][4]. It has been recently reported that the ether lipid ET-18-OCH3 promotes apoptosis in human myeloid leukaemic cells [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic ether phospholipids seem to constitute a novel class of anti-tumour agents [1]. The ether lipid 1-octadecyl-2-methyl-racglycero-3-phosphocholine (ET-1 8-OCH3) is a synthetic analogue of 2-lysophosphatidylcholine and acts as an strong anti-tumour agent [2][3][4]. It has been recently reported that the ether lipid ET-18-OCH3 promotes apoptosis in human myeloid leukaemic cells [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic ether lipid analogues of platelet‐activating factor (1‐ O ‐alkyl‐2‐ O ‐acetyl‐ sn ‐glycero‐3‐phosphocholine, PAF) have been found to be selectively cytotoxic to tumour cells (Andreesen et al , 1978; Okamoto et al , 1987). One of them, 1‐octadecyl‐2‐methyl‐ rac ‐glycero‐3‐phosphocholine (ET‐18‐OCH 3 ), has been used to purge leukaemic cells from remission marrows in acute leukaemia (Vogler et al , 1992) and behaves as a promising anticancer drug (Dietzfelbinger et al , 1993; Houlihan et al , 1995).…”
Section: Introductionmentioning
confidence: 99%